OCAI ANALYSIS OF ORGANIZATIONAL CULTURE AS A REFLECTION OF BUSINESS SUSTAINABILITY (STUDY ON TRIATMA MULYA UNIVERSITY) - Dwiyanti, Ni Made Christine; Ni Luh Putu Agustini Karta; Erna Wiles; Jimmy Harry Putu Suarthana (Bajang Institute, 2025)
Triatma Surya Jaya Foundation (YTSJ), which manages education ranging from early childhood to postgraduate education established in 1992, is very thick with an organizational culture that upholds kinship. This organizational culture gives colour to every activity carried out to achieve the vision, mission, goals, and objectives of the organization. The purpose of this research is to analyse the organizational culture of Triatma Mulya University (UNTRIM) and identify whether it reflects the sustainability of the organization in the future. The respondents of this study were 173 employees of UNTRIM. Data validity test and descriptive analysis showed that only 149 respondents' data were valid for further analysis. Organizational culture was analysed by referring to the theory of Cameron and Quinn (2006), where there are four organizational cultures namely hierarchy, market, clan, and adhocracy. The instrument for processing this data is the Organizational Culture Assessment Instrument (OCAI) analysis, with six key dimensions of organizational culture, consisting of 1) dominant characteristics, 2) organizational leadership, 3) employee management, 4) organizational glue, 5) strategic emphasis, and 6) success criteria. The finding of this research is that the organizational culture at UNTRIM is CLAN. In CLAN organizational culture, UNTRIM governance is more collaborative oriented, conducted by leaders who act as mentors, facilitators, and team builders so that good communication is formed, and high commitment to achieve organizational goals is built. This research shows that UNTRIM also gives enough priority to the market culture that can increase the spirit of competition, consistency, and efficiency to achieve goals within timelines. This is also a reflection of the sustainability of the UNTRIM organization